2018
DOI: 10.3126/jpan.v6i1.21768
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Post Traumatic Stress Disorder and Depression among Nepalese Combatants during Armed Insurgency

Abstract: Introduction: Mental illness is major global public health problem affecting over 450 million people, most of whom live in developing countries. Nepal just overcame ten years long conflict situation. Post-traumatic stress disorder (PTSD) and depression is most prevalent in conflict inflicted areas as per most literatures. Much is not known about the psychological effects of the conflict situation, even after six years of peace process in Nepalese context.Material and Method: This is a cross sectional descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Present study has not showed the association between PTSD and age group as well as education of respondents which was the same in a study of Rawal et al 12 However, there was significant association between PTSD and years of service, shown by Chi-Square value of 21.575 with p-value of 0.00 between PTSD and years of service (i.e., significant) which supports the findings of Rawal et al 12 Similarly, there was also association between the rank and PTSD with the Chi-Square value of 44.184 with p-value of 0.01 showing rank affect the PTSD. It could be due to the experience, their coping mechanism, environmental factors, lifestyle, family support and many more.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Present study has not showed the association between PTSD and age group as well as education of respondents which was the same in a study of Rawal et al 12 However, there was significant association between PTSD and years of service, shown by Chi-Square value of 21.575 with p-value of 0.00 between PTSD and years of service (i.e., significant) which supports the findings of Rawal et al 12 Similarly, there was also association between the rank and PTSD with the Chi-Square value of 44.184 with p-value of 0.01 showing rank affect the PTSD. It could be due to the experience, their coping mechanism, environmental factors, lifestyle, family support and many more.…”
Section: Discussionsupporting
confidence: 56%
“…In the study PTSD was based on validated standardized tool PCL-M with the cut off scale of greater or equal to 50. It was found that only 9% fulfill the criteria of PTSD which is less than study of Rawal et al (2018) 12 where 21.9% of PTSD was found, in mid 1990s which was conducted after 6 years of post-insurgency. Similar differences of PTSD was found in the study conducted among US military personnel and veterans with baseline and follow-up (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) where data was collected approximately every 3 years later, were found to have PTSD though the percentage varies.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations